Investigating the relationship of hardness and flow stress in metal forming. (15th October 2022) - Rudnytskyj, André; Varga, Markus; Krenn, Stefan; Vorlaufer, Georg; Leimhofer, Josef; Jech, Martin; Gachot, Carsten
Abstract: Hardness is routinely utilised to link the bulk material properties to surface contact mechanics. Besides possible differences in the material properties between bulk and surface, there is no established relation between hardness and the thermo-viscoplastic flow stress of materials used in the context of metal forming processes. The purpose of this study is to investigate such relationship using 6061 and 6016 aluminium alloys manufactured by hot rolling. Optical microscopy and Vickers hardness tests at different loads and temperatures ranging from 22 °C up to 450 °C were carried out. A time-dependent Finite Element model of an indentation using thermo-viscoplastic material model based on bulk samples was developed and compared with experiments. Overall, no significant difference between bulk and surface for neither alloy was experimentally identified. The hardness decrease with temperature of the alloys is quantified and ready-to-use constraint factor maps associating the thermo-viscoplastic flow stress with hardness of the materials are presented. The numerical model allowed visualisation of viscoplastic effects, whereas comparisons to the experiments in terms of hardness and topography validated the model and constitutive equations. Constitutive equations derived from compression tests of bulk samples can confidently describe deformation at the surface level and so, be used to develop a contact model in the tribological context of metal forming. Graphical abstract: Highlights: Hardness from 22 °C to 450 °C are measured for 6061 and 6016 aluminium alloys. Constraint factor dependence on thermo-viscoplastic conditions is quantified. Time-dependent indentation model is developed and compared with experiments. Bulk-based thermo-viscoplastic material models can describe surface deformation.